ANALISA ZAT PEWARNA RHODAMIN B PADA LIPSTIK DAN TINGKAT PENGETAHUAN, SIKAP DAN TINDAKAN PEDAGANG KOSMETIK TENTANG BAHAYA RHODAMIN B DI PASAR RAMAI KOTA MEDAN TAHUN 2013 - winda rukmana; indra chahaya; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
Rhodamin B synthetic dyes are substances commonly used in the textile and paper industries. Rhodamin B is often misused to food dye and coloring cosmetics such as syrup, lipstick, rouge cheeks and others. The purpose of this research is to know the existence of substance dyes rhodamin B in lipstick and a level of knowledge, attitudes and actions about the dangers of cosmetic merchant rhodamin B in the Pasar Ramai town of Medan. The method used is descriptive in nature survey to find out the whereabouts of rhodamin B dye substances on lipstick and to find out the level of knowledge, attitudes and actions about the dangers of cosmetic merchant rhodamin B in the Pasar Ramai town of Medan. The research results of dye rhodamin B in Lipstick by using paper chromatography in 10 samples of lipstick are examined, there is no containing rhodamin b. This is in accordance with the regulation of the Minister of health RI Numbers. 239/Men. Kes/Per/V/85 that states rhodamin B is one of the substances are dangerous, so the colors are not allowed their use. For the level of knowledge, attitudes and actions about the dangers of cosmetic merchant rhodamin B in the Pasar Ramai town of Medan which is of thirty merchant cosmetics, 14 persons have knowledge of good, as many as 17 people have good attitude and as many as 24 people have less good action on the danger of rhodamin b. The conclusions of this study are of 10 samples of lipstick are examined, there is no containing rhodamin b. cosmetics traders in the Pasar Ramai knowledge many about the dangers of rhodamin B field is classified as moderate, the attitude of traders crowded markets cosmetics in the field about the dangers of rhodamin B belongs to both the merchant and the lively market in the field of cosmetics on the danger of rhodamin B is less good. Keywords: Rhodamin B, knowledge, attitude, Action